Penyelesaian Sengketa Perbankan Syariah di Luar Lembaga Peradilan - Apriyanti; Iksan; Kasmar (Jurnal Hukum Lex Generalis, 2025)
Sharia banking in Indonesia faces increasingly complex dispute dynamics. Alternative dispute resolution outside the judiciary, such as mediation, arbitration, or through the National Sharia Arbitration Board (BASYARNAS), is considered more in line with Islamic justice principles. This article uses a normative method to examine the effectiveness of non-litigation dispute resolution in Islamic banking. The analysis shows that out-of-court settlement is more efficient, faster, and consistent with sharia values, although stronger regulatory support is needed.